Valoración clínica y parasitológica del tití gris (Primates: Cebidae: Saguinus leucopus) en dos poblaciones naturalespresentes en San Carlos y San Rafael (Antioquia, Colombia) (2014)
ABSTRACT: While much of the natural history of Neotropical primates has been revealed through studies conducted in captive individuals, environmental factors may impose ecological and physiological differences in free-range populations. For the white-footed tamarin (Saguinus leucopus), a primate endemic to Northwest Colombia, physiological parameters that have been assessed in captivity still remain to be measured in free-range populations. In order to diagnose the health status of this species in a natural environment, we assessed several external traits, measured hematological and blood-chemistry values, and characterized the parasite community of two natural populations. Despite the identification of eleven different parasite taxa and wide distribution of filaria and Trypanosoma spp., we faieled to detect signs of poor health condition. Substantial differences were found between captive and free-range tamarin populations in the composition of their parasite communities. Likewise, hematological and blood-chemistry profiles differed between free-range populations and even between neighboring social groups, suggesting a role of environmental factors in the physiological response. However, none of the physiological parameters varied as a response to parasite infection. Our results revealed a high diversity of parasites and elevated rates of parasitic infections in natural populations of S. leucopus, that do not seem to be associated with indicators of health conditions. Future studies should emphasize on ecological, genetic and demographic factors that determine the health conditions of S. leucopus in the wild. Lastly, geographic variation of physiological profiles and parasite distribution, as well as epidemiological differences between captive and wild populations, should be incorporated in rehabilitation plans of captive tamarins in order to restrict the transmission of infectious agents between populations.